ANALYSIS OF DIVERSIFICATION AND OPTIMUM PRICING STRATEGY OF INDUSTRIAL PRODUCTS (Conferencea, 2023)
In the article, some approaches to the diversification of industrial products at optimal prices were studied, one of the main results of industrial diversification was developed, scientific proposals and practical recommendations were developed regarding the development of diversified industrial products, processes of diversification of industrial products in production.